2016
DOI: 10.1155/2016/5954394
|View full text |Cite
|
Sign up to set email alerts
|

Parasitaemia and Its Relation to Hematological Parameters and Liver Function among Patients Malaria in Abs, Hajjah, Northwest Yemen

Abstract: Plasmodium falciparum malaria is the most common infection in Yemen. The present study aims to investigate changes in hematological and hepatic function indices of P. falciparum infected individuals. This study included 67 suspected falciparum malarial patients attended in clinics and rural Abs Hospital (Tehama, Hajjah), Yemen, from October 2013 to April 2014. The diagnosis of malaria was confirmed by thick and thin film with Giemsa staining of malaria parasite. Hematological parameters and serum levels of asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 12 publications
(14 reference statements)
7
51
1
Order By: Relevance
“…This may be the possible mechanism of reduction of hemoglobin level in malaria patients (8) . Hemoglobin was significantly reduced in malaria may be due to reduced synthesis of red blood cells (RBCs) and increased breakdown of red cells by parasites (9,1,10) . Anemia is one of the most common complications of malaria, occurring as a direct and indirect consequence of the infection and destruction of erythrocytes by Plasmodium parasites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may be the possible mechanism of reduction of hemoglobin level in malaria patients (8) . Hemoglobin was significantly reduced in malaria may be due to reduced synthesis of red blood cells (RBCs) and increased breakdown of red cells by parasites (9,1,10) . Anemia is one of the most common complications of malaria, occurring as a direct and indirect consequence of the infection and destruction of erythrocytes by Plasmodium parasites.…”
Section: Discussionmentioning
confidence: 99%
“…WHO reported that low leukocyte count may be used as probable indicator for malaria in endemic countries. The decrease in lymphocyte counts associated with malaria may be due to reflecting redistribution of lymphocytes with sequestration in the spleen (10) . In our study we found increased serum bilirubin, AST and ALT activities in patients suffering from malaria as compared to control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be attributed to the low-tomoderate levels of parasitaemia in uncomplicated malaria cases. In another context, thrombocytopenia was signi cantly associated with falciparum malaria in Hajjah governorate, northwest of Yemen [61]. A signi cant association was also reported among Kenyan and Nigerian children [21,62].…”
Section: Sociodemographic and Risk Factors Associated With Falciparummentioning
confidence: 91%